An integrated approach to doped thin films with strain-tunable magnetic anisotropy: powder synthesis, target preparation and pulsed laser deposition of Bi:YIG. Issue 1 (2nd January 2017) - Sellappan, Pathikumar; Tang, Chi; Shi, Jing; Garay, Javier E.
Abstract : We present a synthesis/processing method for fabricating ferrimagnetic insulator (Bi-doped yttrium iron garnet) thin films with tunable magnetic anisotropy. Since the desired magnetic properties rely on controllable thickness and successful doping, we pay attention to the entire synthesis/processing procedure (nanopowder synthesis, nanocrystalline target preparation and pulsed laser deposition (PLD)). Atomically flat films were deposited by PLD on (111)-orientated yttrium aluminum garnet. We show a significant enhancement of perpendicular anisotropy in the films, caused by strain-induced anisotropy. In addition, the perpendicular anisotropy is tunable by decreasing the film thickness and overwhelms the shape anisotropy at a critical thickness of 3.5 nm. GRAPHICAL ABSTRACT: IMPACT STATEMENT Strain-induced perpendicular magnetic anisotropy (PMA) in heavily Bi substituted YIG films for ferrimagnetic insulator based spintronic studies and devices.